Teachers' and Students' Points of View on Audio for Listening Skills in Metacognitive Strategy Instruction - Bella Ayu Herawati; Delsa Miranty; Eri Rahmawati (English Department - Universitas Sultan Ageng Tirtayasa, 2022)
Listening is one of the four skills in English, which plays the most important role. Listening is a skill that everyone must master because it is how everyone receives and retrieves ideas. In honing listening skills, students need the right strategies and materials to understand what they are learning. In honing listening skills, students need the right strategies and materials to understand what they are learning. In honing listening skills, the teacher also plays an important role. The teacher's role is to determine the strategies and materials to teach students in class. One strategy that can be applied is a metacognitive strategy. Therefore, the use of metacognitive strategies can be applied by teachers to teach in the eleventh grade by using interesting materials or tools such as using audio, namely songs. By using metacognitive strategies, learning activities will not only be teacher-centered but also student-centered as well, and using songs will be able to make learning English fun, and students will become active in learning.